Occurrence of Helicoverpa armigera (Hübner, 1808) on citrus in the state of Sao Paulo, Brazil - Bueno, Regiane Cristina Oliveira de Freitas [UNESP]; Yamamoto, Pedro Takao; Carvalho, Marina Mouzinho [UNESP]; Bueno, Nádia Maebara [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
The occurrence of Helicoverpa armigera (Hübner, 1808) was first reported in citrus orchard in the state of São Paulo (SP). High infestation levels of H. armigera were observed in October 2012, in the city of Botucatu, SP. The larvae was fed of all parts of the plants. The injuries on the leaves caused drastic reduction in the leaf area and the fruits attack occurred from an early stage of development to the ripe fruit. Thus, the first occurrence of H. armigera in this citrus culture adds to the list of hosts of this pest, and is of great importance, because it confirms H. armigera potential dispersion and polyphagia.

A ocorrência de Helicoverpa armigera (Hübner, 1808) foi relatada pela primeira vez em pomar comercial de cítrus no Estado de São Paulo (SP). Altos níveis de infestação de H. armigera foram observados em outubro de 2012, na cidade de Botucatu-SP. As larvas alimentaram-se em todas as partes de plantas. As lesões nas folhas causaram drástica redução da área foliar, e o ataque aos frutos ocorreu a partir do estágio inicial de desenvolvimento até a fase do fruto maduro. Assim, o relato da primeira ocorrência de H. armigera acrescenta a cultura de citros à lista de hospedeiros desta praga, e é de grande importância, pois confirma a polifagia e o potencial de dispersão de H. armigera.
Ocorrência de Helicoverpa armigera (Hübner, 1808) em citros no estado de São Paulo, Brasil
Keywords: Praga quarentenária; Heliothinae; Lepidoptera; Noctuidae; citros; Quarantine pest; Heliothinae; Lepidoptera; Noctuidae; citrus